Simulating the impact of electron beam energy deposition on lead target temperature - Walid Oueslati (Nuclear Analysis)
This study delves into the thermal dynamics induced by an electron beam sourced from the CIRCE III accelerator, focusing on a lead target previously employed at the National Centre for Nuclear Science and Technology (CNSTN) in Tunisia for neutron and photon production. Leveraging FLUKA software, we simulate the intricate interplay between electrons and the target surface, analyzing variations in deposited energy across different target thicknesses. Beyond elucidating the electron-target interaction, our investigation extends to predicting crucial parameters such as the maximum operational threshold and surface temperature distribution of the target. To achieve this, a computational model harnessing the finite volume method is employed, offering insights into the thermal response dynamics and paving the way for optimized operational protocols and target design refinements. Through this comprehensive analysis, we aim to advance the understanding of thermal phenomena in electron-target interactions, thereby bolstering the efficiency and safety of particle accelerator operations in diverse scientific applications.